Dampak Modal Intelektual Hijau terhadap Pengungkapan Sukarela Emisi Karbon - Oktris, Lin (Indonesian Journal of Accounting and Governance, 2018)
The purpose of this research is to analyze the effect of green intellectual capital on voluntary carbonemissions disclosure in IDX listed non financial companies in 2010-2014 with 40 companies samples.This research focuses on internal aspects side. This research methodology is multiple regressionanalysis. The results show that green intellectual capital have positive effect on voluntary carbonemissions disclosures. The results have contribution in disclosure of carbon emissions research foreducators and stakeholders. The novelty of this research is to analyze new variables such as greenintellectual capital. There are only 40 sample companiesbecause the disclosure of carbon emissions inIndonesia is still voluntary. Because samples only from Indonesia companies so the results cannot begeneralized in ASEAN countries, Forfuture research, researcher can use primary data to measuregreen intellectual capital so that it reflects the perception of the company.